Unraveling the role of support membrane chemistry and pore properties on the formation of thin-film composite polyamide membranes - Lim, Yu Jie; Goh, Kunli; Lai, Gwo Sung; Zhao, Yali; Torres, Jaume; Wang, Rong (Journal of membrane science, 2021)
Nanoscale characteristics of the polyamide layer are key towards the high desalination performance of thin-film composite reverse osmosis (TFC-RO) membranes. Further advancements in the performance of TFC membranes necessitate a comprehensive understanding of the desired polyamide characteristics and its formation mechanisms. Empirical evidence has shown that the properties of the support layer is as equally important as the interfacial polymerization (IP) conditions in the fabrication of high permselectivity TFC membranes for desalination. Herein, we discuss the properties of polyamide layers formed using identical IP conditions over support membranes of different polymers and chemistries (polyethersulfone, polyetherimide and polysulfone) under fairly similar surface pore properties. The characteristics of the polyamide layers formed thereon displayed different physicochemical properties. It is postulated that the support membrane chemistry actually affects the IP reaction and polyamide formation by controlling the amine diffusion speed as well as the breadth of the IP reaction zone (i.e., the region between the interface and the furthest point in which the reaction occurs). Transmission electron microscopy analyses further revealed the nanoscale differences in the polyamide layer (heights ranging from 50 to 200 nm), including intrinsic thickness of basal layer (~10–35 nm) and leaf-like top layer (~20–85 nm), as well as the presence of nanovoids. Finally, we propose a conceptual model to underline the role of support membrane chemistry in the IP reaction, and consequently the formation mechanism of the nanoscale polyamide features. The mechanistic insights from this study are expected to provide more understanding towards a better control over the fabrication of polyamide layers for TFC membranes. The findings in this work are also expected to facilitate tailoring polyamide layers for specific osmotically driven processes. [Display omitted] •Support membrane chemistry affects MPD diffusion and partitioning extent in IP.•TEM and SEM analyses revealed changes in the polyamide (PA) nanoscale morphology.•PA layer of TFC-PES membrane was thin and smooth without any nanovoids.•PA layer of TFC-PSf membrane had thick base, thin leaves and multi-layer nanovoids.•PA layer of TFC-PEI membrane had thin basal layer with clumpy roof-like top layer.